Modeling of lithium granule injection in NSTX with M3D-C1. (August 2017) - Fil, A.; Kolemen, E.; Bortolon, A.; Ferraro, N.; Jardin, S.; Parks, P.B.; Lunsford, R.; Maingi, R.
Highlights: A new ablation model for Li granules is implemented in the MHD code M3D-C1. 2D simulations of Li granule injections in NSTX realistic H-mode plasmas are performed. Large granules lead to a high pedestal pressure increase, favourable for ELM-pacing. Velocity and angle of injection can be chosen to maximize the granule deposition at the pedestal top. Abstract: In this paper we present initial simulations of pedestal control by Lithium Granule Injection (LGI) in NSTX. A model for small granule ablation has been implemented in the M3D-C1 code[1], allowing the simulation of realistic Lithium granule injections. 2D simulations in NSTX L-mode and H-mode plasmas are done and the effect of granule size, injection angle and velocity on the pedestal gradient increase are studied. For H-mode cases, the amplitude of the local pressure perturbation caused by the granules is highly dependent on the solid granule size. In our simulations, reducing the granule injection velocity allows one to inject more particles at the pedestal top.